MEMBANGUN INTENSI BERWIRAUSAHA MELALUI ADVERSITY QUOTIENT, SELF EFFICACY, DAN NEED FOR ACHIEVEMENT - Agung Wahyu Handaru; Widya Parimita; Inka Winarni Mufdhalifah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2015)
This study has identified the recent condition of entrepreneurial intention among one hundred and two students at fashion design school in Jakarta. Result of linier regression test showed that students’ adversity quotient can shape their entrepreneurial intention. Second, students’ self-efficacy is also shaping their entrepreneurial intention, and third, students’ need for achievement contributes in building their entrepreneurial intention. Another finding showed that students’ adversity quotient, self-efficacy, and need for achievement altogether can shape students’ entrepreneurial intention with the cumulative of 46.2%.